×

Hello! Socratic's Terms of Service and Privacy Policy have been updated, which will be automatically effective on October 6, 2018. Please contact hello@socratic.com with any questions.

How do you solve #2^(2x) + 2^(x + 2) - 12 = 0#?

1 Answer
Oct 25, 2015

Answer:

#x=1#

Explanation:

First, rearrange the equation like this:

#2^(2x) + 2^(x + 2) - 12 = 0#

#(2^x)^2 + 4(2^x) - 12 = 0#

Now, treat this like a quadratic equation by substituting #2^x=s#:

#s^2+4s-12=0#

#(s+6)(s-2)=0#

#s=-6# or #s=2#

Now, go back to the substitution:

#2^x=s#

#2^x=-6# or #2^x=2#

Since #2^x# can never equal a negative number, we can rule out the first solution.

However, the second solution results in #x=1#

Hope that helped